Transcriptional Repression and Protein Degradation of the Ca2+-Activated K+ Channel KCa1.1 by Androgen Receptor Inhibition in Human Breast Cancer Cells - Khatun, Anowara; Shimozawa, Motoki; Kito, Hiroaki; Kawaguchi, Mayu; Fujimoto, Mayu; Ri, Moe; Kajikuri, Junko; Niwa, Satomi; Fujii, Masanori; Ohya, Susumu (Frontiers in Physiology, 2018)
The large-conductance Ca2+-activated K+ channel KCa1.1 plays an important role in the promotion of breast cancer cell proliferation and metastasis. The androgen receptor (AR) is proposed as a therapeutic target for AR-positive advanced triple-negative breast cancer. We herein investigated the effects of a treatment with antiandrogens on the functional activity, activation kinetics, transcriptional expression, and protein degradation of KCa1.1 in human breast cancer MDA-MB-453 cells using real-time PCR, Western blotting, voltage-sensitive dye imaging, and whole-cell patch clamp recording. A treatment with the antiandrogen bicalutamide or enzalutamide for 48 hr significantly suppressed 1) depolarization responses induced by paxilline (PAX), a specific KCa1.1 blocker and 2) PAX-sensitive outward currents induced by the depolarizing voltage step. The expression levels of KCa1.1 transcripts and proteins were significantly decreased in MDA-MB-453 cells, and the protein degradation of KCa1.1 mainly contributed to reductions in KCa1.1 activity. Among the eight regulatory β and γ subunits, LRRC26 alone was expressed at high levels in MDA-MB-453 cells and primary and metastatic breast cancer tissues, whereas no significant changes were observed in the expression levels of LRRC26 and activation kinetics of PAX-sensitive outward currents in MDA-MB-453 cells by the treatment with antiandrogens. The treatment with antiandrogens up-regulated the expression of the ubiquitin E3 ligases, FBW7, MDM2, and MDM4 in MDA-MB-453 cells, and the protein degradation of KCa1.1 was significantly inhibited by the respective siRNA-mediated blockade of FBW7 and MDM2. Based on these results, we concluded that KCa1.1 is an androgen-responsive gene in AR-positive breast cancer cells, and its down-regulation through enhancements in its protein degradation by FBW7 and/or MDM2 may contribute, at least in part, to the antiproliferative and antimetastatic effects of antiandrogens in breast cancer cells.